UPAYA PENDEKATAN RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA KECELAKAAN LALU LINTAS DI WILAYAH HUKUM POLRES JAKARTA BARAT - Jasman; Rahmat, Diding (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
The resolution of criminal cases through restorative justice at the investigation stage is regulated in the Chief of Police Circular Letter Number 8 of 2018 concerning the Implementation of Restorative Justice in the Settlement of Criminal Cases. This circular stipulates that cases must be resolved through restorative justice before the Notification Letter on the Commencement of Investigation (SPDP) is sent to the Public Prosecutor. Additionally, the application of restorative justice is only applicable to crimes that do not result in human victims, leading to various challenges in its implementation.This study employs a normative-empirical juridical method with a legislative and case approach. Primary data collection was conducted through field research, while secondary data was obtained through literature review. The research findings indicate that the implementation of restorative justice in resolving serious traffic accident cases at the West Jakarta Metro Police was carried out by investigators after a peace agreement was reached between the perpetrator and the victim’s family. However, this reconciliation occurred after the investigators had already sent the SPDP to the West Jakarta Attorney General’s Office, resulting in the discontinuation of the case proceedings.Several factors influence the implementation of restorative justice in resolving serious traffic accident cases, including law enforcement factors, legal substance factors, and legal culture factors. Law enforcement factors relate to the knowledge and understanding of investigators regarding the applicable laws and regulations. Legal substance factors refer to the content of the Chief of Police Circular Letter, which sets material requirements that do not accommodate the resolution of cases involving human victims, as well as formal requirements that limit the application of restorative justice only to the investigation stage before the SPDP is sent. Meanwhile, legal culture factors reflect the values, attitudes, and behaviors of society in social life, which also influence decisions to resolve traffic accident cases through a restorative justice approach. The combination of these three factors demonstrates the complexity of implementing restorative justice, particularly in cases involving loss of life, highlighting the need for further adjustments and evaluation of existing regulations.